2017
DOI: 10.1097/nmc.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Embolism

Abstract: Amniotic fluid embolism (AFE) is a rare but serious and potentially deadly complication of pregnancy that is unpreventable and unpredictable. Most AFE events occur during labor; however, approximately one third happen during the immediate postpartum period. Presentation is abrupt and thought to be an abnormal response to fetal materials entering maternal circulation through the placental insertion site. Care providers must recognize the signs and symptoms of AFE and react quickly to treat potential complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Most of these occur during labor; but about one third happen during the immediate postpartum period. 3 This patient has no hypoxia, hypotension, or coagulopathy and is outside the expected time frame for amniotic fluid embolism, meaning we can likely remove it from the differential.…”
Section: Case Discussion (Attending Discussion)mentioning
confidence: 99%
“…Most of these occur during labor; but about one third happen during the immediate postpartum period. 3 This patient has no hypoxia, hypotension, or coagulopathy and is outside the expected time frame for amniotic fluid embolism, meaning we can likely remove it from the differential.…”
Section: Case Discussion (Attending Discussion)mentioning
confidence: 99%
“…Some authors have suggested the ventricular dysfunction is secondary to either pulmonary hypertension caused by serotonin and thromboxane or systemic hypotension caused by vagal stimulation [ 1 , 11 ]. It has been proposed that Atropine and Ondansetron may act to block serotonin and vagal stimulation improving cardiovascular function rather than simply providing cardiovascular support [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic fluid embolism (AFE) is a rare, unpredictable, and potentially devastating complication of childbirth, in which amniotic fluid, fetal cells, hair, or other types of debris enter into the maternal pulmonary circulation, causing cardiovascular collapse [ 1 , 2 ]. The incidence of AFE ranges from 1 : 15,200 to 1 : 53,800 [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations